Exploring the Knowledge and Attitude of the Taxi Drivers in the Field of Traffic Rules and Regulations. (10th November 2022) - Khani Jeihooni, Ali; Rakhshani, Tayebeh; Keshavarzi, Arash; Kashfi, Seyyed Mansour; Frarouei, Mohammad; Kamyab, Amirhossein
Abstract : Background . In all countries, the knowledge of driving guidelines is the most important and critical mechanism to ensure the safety of drivers. Naturally, it is expected that more knowledge and attitude towards driving laws would result in fewer driving violations. The aim of this research is to investigate both the knowledge and attitude of taxi drivers in the field of traffic rules and regulations in Shiraz city, Fars province, in 2019. Methods . This research is a cross-sectional study, based on which about 1077 taxi drivers were randomly chosen in Shiraz city, Iran. The data collection tool is a demographic information questionnaire and a questionnaire on driving guidance. After collecting these questionnaires, the obtained data were entered into SPSS version 20 and then analyzed by descriptive analyses (mean, standard deviation, and percentage). Afterward, the independent t -test, one-way ANOVA, and Pearson correlation coefficient are implemented and investigated. Results . The mean and standard deviation of knowledge score in drivers were about 26.8 ± 55.2 while the mean and standard deviation of drivers' attitude were about 98.16 ± 59.3. The results showed that there was a significant relationship between the variables studied ( R  = −0.07; P = 0.02 ) and drivers' attitudes toward driving (P = 0.01 ). Conclusion . The results of this research show that the mean scores of knowledge and attitude of taxi drivers in Shiraz city are moderate in terms of driving rules and regulations; moreover, among taxi drivers of increasing age, the average score of knowledge was lower.